Factors Influencing Local Tourists’ Decision-making on Choosing a Destination: a Case of Azerbaijan - Seyidov, Javid; Adomaitienė, Roma (Ekonomika, 2017)
The purpose of the article is to analyse factors influencing the behaviour and decision-making of local tourists in choosing Azerbaijan as a destination. The main attributes, elements and types of tourism destinations are analysed. The understanding of consumer behaviour is defined and the peculiarities of decision-making process are presented. The main internal and external factors influencing tourist’s behaviour and decision-making are summarised. The current situation of tourism in Azerbaijan is examined. The analysis of social, cultural, personal and psychological factors influencing the decision-making of local Azerbaijani tourists to travel to various types of tourism destinations with different attributes like, attractions, available amenities, accessibility, image, price and human resources is done. The research includes both primary and secondary data. Secondary data is used to give insight to the topic and assess conclusions. Primary data is collected by surveying domestic travellers of Azerbaijan. Survey results are analysed by implying descriptive statistics, non-parametric tests and Factor analysis. The research results show that the age, monthly income and marital status of local Azerbaijani travellers affect their travel behaviour especially in the duration of their trip. Destination amenities, tourism infrastructure, environmental features, human resources and price are the important attributes for local tourists in choosing tourism destination.
Keywords: consumer behaviour; decision-making; tourism destination; tourism in Azerbaijan; Azerbaijani tourist